Characterization of dairy farming, feed types and management practices in Rwanda - Sibiko, Kenneth W.; Munyentwari, Joseph Mbuta; Nyawira, Sylvia (2024)
This research study is part of the LSIL-Rwanda project titled "Developing Climate-Smart Management Strategies to Improve the Sustainability of Smallholder Dairy Cattle Production Systems in Rwanda." The aim is to understand the socio-economic characteristics and the extent of adoption of improved forage grasses and climate-smart agriculture (CSA) among dairy farmers in the Burera, Nyagatare, and Nyanza districts of Rwanda. The results will be used to cluster and develop a typology for the farms, proposing appropriate improvements to enhance feed availability and milk production for better economic and environmental sustainability in the project sites. This study builds on cross-sectional survey data from a sample of 220 smallholders in the three districts